2001
DOI: 10.1136/jnnp.71.6.809
|View full text |Cite
|
Sign up to set email alerts
|

Cortical excitability and sleep deprivation: a transcranial magnetic stimulation study

Abstract: The objective was to assess the changes in cortical excitability after sleep deprivation in normal subjects. Sleep deprivation activates EEG epileptiform activity in an unknown way. Transcranial magnetic stimulation (TMS) can inform on the excitability of the primary motor cortex. Eight healthy subjects (four men and four women) were studied. Transcranial magnetic stimulation (single and paired) was performed by a focal coil over the primary motor cortex, at the "hot spot" for the right first dorsal interosseo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 20 publications
5
55
1
2
Order By: Relevance
“…However, an increase in cortical excitability induced by total sleep deprivation has been documented by some studies in healthy subjects [17,18,46] as well as in epileptic patients [20,21,47]. In particular, Scalise et al [18] reported a reduction of both SP duration and ICI after total sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an increase in cortical excitability induced by total sleep deprivation has been documented by some studies in healthy subjects [17,18,46] as well as in epileptic patients [20,21,47]. In particular, Scalise et al [18] reported a reduction of both SP duration and ICI after total sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the effects of total sleep deprivation on human motor cortex have been explored by means of TMS in normal individuals with conflicting results, mainly due to partial different methodological protocols utilized [17][18][19]45]. However, an increase in cortical excitability induced by total sleep deprivation has been documented by some studies in healthy subjects [17,18,46] as well as in epileptic patients [20,21,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,17,32 Because surface electromyography (EMG) is used to measure changes in corticomotor excitability of the target muscle, TMS measures may also vary between test sessions, due to differences in electrode placement and/ or skin impedance. Though reliability of TMS has been established for upper extremity muscles such as the biceps and first dorsal interosseus, 17,[20][21][22] measurement error may be magnified when measuring corticomotor excitability of the gluteus maximus, a large muscle with a small M1 representational area.…”
Section: T T Methodsmentioning
confidence: 99%
“…It has been reported that corticospinal fibers are normally activated by magnetic stimulation, while motor excitability is decreased during different sleep stages [17,33]. In contrast, other authors [160] have observed that in normal subjects, 24 hours of sleep deprivation produce an increase in motor excitability as studied by TMS in two sessions, namely, before and after sleep deprivation. The different effects on motor excitability of sleep deprivation could be due to the differences in study methods and objectives.…”
Section: Consciousness and Epilepsymentioning
confidence: 73%